آثر رسملة الموارد البشرية وفق نموذج التكلفة التاريخية على الميزانية الاقتصادية - دراسة حالة شركة التوزيع الكهرباء والغاز الوادي - 2019- - منال, زهري; خالدة, زهري; بسام, بن ياية; حاج مسعود, دشري (University of eloued جامعة الوادي, 2021)
"هدفت هذه الدراسة إلى إبراز أثر رسملة الموارد البشرية وفق نموذج التكلفة التاريخية على المؤسسة الاقتصادية, فإن نجاح المشاريع الاقتصادية في تحقيق أهدافها يعتمد بدرجة كبيرة على كفاءة وفعالية الموارد البشرية العاملة بها من حيث القياس والتكاليف الاختيار والتعيين والتدريب والتطوير الأصول البشرية وتعديل القيمة الاقتصادية لها, فقد سعت الكثير من المؤسسات الاقتصادية لتطبيق هذا المفهوم في إطار المحاسبة عن الموارد البشرية حيث ساهم التقدم العلمي في توجيه الفكر المحاسبي إلى إعادة النظر في المعالجة الموارد البشرية. واد ا ركا من الباحثين لأهمية توفر المعلومات عن تلك الموارد البشرية فقد نشطت المحاولات لوضع أسس للمحاسبة عن الموارد البشرية واثبات اعتبار المورد البشري كمورد اقتصادي وبيان أثر على القوائم المالية للمؤسسة ومعرفة أهميته في تحقيق أهداف إست ا رتيجية, إضافة إلى ضرورة اتخاذ الإج ا رءات والسياسات الرسمية من أجل تطبيق محاسبة الموارد البشرية ونخص بالذكر نموذج القياس المحاسبي الذي يعتمد على التكلفة التاريخية, وسنحاول في هذه الد ا رسة إب ا رز أهم النقاط المتعلقة ب محاسبة الموارد البشرية وكيفية معالجتها وتسجيلاتها المحاسبية بشركة سونلغاز بالوادي لسنة 2019 . ومن أبرز النتائج د ا رستنا أن محاسبة الموارد البشرية هي جزء رئيسي من نظام المعلومات المحاسبية حيث تختص بتوفير البيانات المتعلقة بالقياس قيمة الموارد البشرية وتجميعها وتحليلها. ""This study aimed to highlight the impact of capitalization of human resources according to the historical cost model on the economic institution. Many economic institutions have sought to apply this concept in the framework of accounting for human resources, where scientific progress has contributed to directing accounting thought to a reconsideration of the treatment of human resources. Realizing the importance of the availability of information on these human resources, attempts have been made to lay the foundations for accounting for human resources and to prove that the human resource is considered an economic resource and to indicate its impact on the financial statements of the institution and to know its importance in achieving strategic goals, in addition to the need to take official procedures and policies in order to apply resource accounting In particular, we mention the accounting measurement model that depends on the historical cost. In this study, we will try to highlight the most important points related to human resource accounting and how to treat it and its accounting records in Sonelgaz Company in the Valley for the year 2019. One of the most prominent results of our study is that human resources accounting is a major part of the accounting information system, as It is concerned with providing, compiling and analyzing data related to the measurement of the value of human resources. "
ماستر محاسبة
Keywords: محاسبة الموارد البشرية, القياس المحاسبي, نظام المعلومات المحاسبية.; human resources accounting, accounting measurement, accounting information system.